2022
DOI: 10.1044/2021_jslhr-21-00230
|View full text |Cite
|
Sign up to set email alerts
|

Listening Effort in Cochlear Implant Users: The Effect of Speech Intelligibility, Noise Reduction Processing, and Working Memory Capacity on the Pupil Dilation Response

Abstract: Purpose: This study aimed to evaluate the effect of speech recognition performance, working memory capacity (WMC), and a noise reduction algorithm (NRA) on listening effort as measured with pupillometry in cochlear implant (CI) users while listening to speech in noise. Method: Speech recognition and pupil responses (peak dilation, peak latency, and release of dilation) were measured during a speech recognition task at three speech-to-noise ratios (SNRs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…It is no news that the same SNR level does not yield same speech recognition scores among NH, HI, and CI listeners, so comparing directly 'tipping points' in terms of their corresponding SNR levels is not thorough enough. Regardless of the difference in SNR levels, NH and HI listeners typically showed the 'tipping point' on their pupillometry psychometric curves at around 40-50% speech intelligibility (Ohlenforst et al, 2017;Wendt et al, 2017;Dingemanse and Goedegebure, 2022). This suggests that even though NH and HI listeners have different speech recognition, they tend to disengage from the task at similar intelligibility level.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is no news that the same SNR level does not yield same speech recognition scores among NH, HI, and CI listeners, so comparing directly 'tipping points' in terms of their corresponding SNR levels is not thorough enough. Regardless of the difference in SNR levels, NH and HI listeners typically showed the 'tipping point' on their pupillometry psychometric curves at around 40-50% speech intelligibility (Ohlenforst et al, 2017;Wendt et al, 2017;Dingemanse and Goedegebure, 2022). This suggests that even though NH and HI listeners have different speech recognition, they tend to disengage from the task at similar intelligibility level.…”
Section: Discussionmentioning
confidence: 98%
“…This study is motivated by the authors intending to resolve anecdotal reports on using pupillometry with CI users in the clinical settings. Past studies have examined CI users' pupillary response at various points on the psychometric curve (Russo et al, 2020;Stronks et al, 2021;Dingemanse and Goedegebure, 2022), however our study is the first to date to approximate a more complete curve by testing multiple points and considering a wide range of individual differences.…”
Section: Practical Considerations In Research and Clinical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has already been suggested that a slower speaking rate and the availability of a relevant semantic context may reduce listening effort in CI users (58,59). Furthermore, listening effort seems to decrease with increasing SNR levels (12,42,60) although, even in favorable listening conditions, listening is still an effort for CI users (60). Considering that listening remains an effort for CI users and the higher listening effort reported in CI compared to controls with normal hearing, it is interesting to further explore the influencing factors as there is still much ambiguity about it.…”
Section: Profile Of Mood States (Poms)mentioning
confidence: 99%